STATUS KONSERVASI BURUNG DI KAWASAN AIR TERJUN TINGKAT TUJUH KABUPATEN ACEH SELATAN - Ulfiyah, Muna; Hanim , Nafisah; Zuraidah, Zuraidah; Eriawati, Eriawati; Ahadi, Rizky (KENANGA : Journal of Biological Sciences and Applied Biology, 2024)
Conservation status of birds can be interpreted as the breeding status of birds or the status of species in protected natural areas. Birds play a crucial role in dispersing various types of plants, such as fruits and seeds. This study aims to identify data on bird species categorized under conservation status in the Seven-Tier Waterfall area of South Aceh Regency, to serve as a basis for conservation actions and bird protection efforts. The methods used in this research include Exploratory Surveys and Point Count. Conservation status refers to the International Union for Conservation of Nature (IUCN) Red List of Threatened Species, and the Ministry of Environment and Forestry Regulation (PERMENLHK) P.106/MENLHK/SETJEN/KUM.1/12/2018. The Convention on International Trade in Endangered Species (CITES) is used to determine national trade status. The results of the study on the conservation status of birds in the Seven-Tier Waterfall area of South Aceh Regency are classified into 3 IUCN categories: LC (Least Concern) with 21 bird species, NT (Near Threatened) with 2 bird species, and VU (Vulnerable) with 2 bird species. Additionally, according to CITES, there are 3 bird species listed in Appendix II.  According to the Ministry of Environment and Forestry Regulation (PERMENLHK) P.106/MENLHK/SETJEN/KUM.1/12/2018, there are 4 protected bird species in the Seven-Tier Waterfall area of South Aceh Regency.